2000
DOI: 10.1002/1521-396x(200012)182:2<607::aid-pssa607>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Transmission Electron Microscopy of Be Implanted Si-Doped GaAs

Abstract: Be ions were implanted into degenerately Si-doped GaAs at 300 keV to a dose of 10 15 cm À2 . The region near the projected range remained crystalline, and subthreshold defects formed at this depth after annealing at 450-500 C. The defects are identified as circular prismatic perfect interstitial loops on the {110} planes, originating after the annealing of defect clusters near 400 C. The Burgers vector of these loops was computed using the comparison of experimental and computed defect intensity profiles. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2000
2000

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…These typical subthreshold defects have been discussed [1], and of interest here are parallelogram-shaped, triangular and line-like defect images also found occasionally in these samples. These typical subthreshold defects have been discussed [1], and of interest here are parallelogram-shaped, triangular and line-like defect images also found occasionally in these samples.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…These typical subthreshold defects have been discussed [1], and of interest here are parallelogram-shaped, triangular and line-like defect images also found occasionally in these samples. These typical subthreshold defects have been discussed [1], and of interest here are parallelogram-shaped, triangular and line-like defect images also found occasionally in these samples.…”
Section: Resultsmentioning
confidence: 54%
“…A recent study of high dose (10 15 cm À2 ) Be implanted Si-doped GaAs showed that extended defects formed only after annealing at 450-500 C and that most of the defects were circular interstitial prismatic dislocation loops on the {110} planes [1]. These are typical subthreshold implantation defects, which form in implanted material prior to amorphization (usually after annealing).…”
Section: Introductionmentioning
confidence: 99%